Efficient Enrichment of Retinal DHA with Dietary Lysophosphatidylcholine-DHA: Potential Application for Retinopathies - Sugasini, Dhavamani (Nutrients, 2020)
Although decreased retinal docosahexaenoic acid (DHA) is a known risk factor for retinopathy, currently available omega-3 fatty acid supplements, which are absorbed as triacylglycerol (TAG), do not significantly enrich retinal DHA. We tested the hypothesis that lysophospahtidylcholine (LPC)-DHA which is absorbed as phospholipid, would efficiently increase retinal DHA because of the presence of LPC-specific transporter at the blood–retina barrier. In normal rats, LPC-DHA and di-DHA phosphatidylcholine (PC), which generates LPC-DHA during digestion, increased retinal DHA by 101% and 45%, respectively, but TAG-DHA had no significant effect at the same dose (40 mg/kg, 30 days). In normal mice, both sn-1 DHA LPC and sn-2 DHA LPC increased retinal DHA by 80%, but free DHA had no effect. Lipase-treated krill oil (which contains LPC-DHA and LPC-EPA (eicosapentaenoic acid), but not normal krill oil (which has little LPC), increased both retinal DHA (+76%) and EPA (100-fold). Fish oil, however, had no effect, whether lipase-treated or not. These studies show that retinal DHA can be efficiently increased by dietary LPC-DHA, but not by TAG-DHA or free DHA. Since DHA is known to be protective against retinopathy and other eye diseases, this study provides a novel nutraceutical approach for the prevention/treatment of these diseases.